A Comparative Study of the Impact of Virtual Space on the Lifestyle of User and Non-User Women in Garmsar City - Galini, Marziyeh; Sedaghati Fard, Mojtaba; Parnian, Shideh (Psychology of Woman Journal, 2025)
Objective: The study aimed to compare the impact of virtual space on the lifestyle of user and non-user women. Methods and Materials: This survey research was conducted among women aged 19 to 59 years in Garmsar City in 2020. The sample included 320 participants, divided equally into two groups of user and non-user women, selected through simple random sampling. Data were collected using a researcher-developed questionnaire with a five-point Likert scale. The validity of the questionnaire was confirmed by experts in the field, and its reliability was assessed through Cronbach’s alpha, yielding an acceptable coefficient. Findings: Significant differences were observed between the two groups of women across six lifestyle indicators (except for marital style). User women exhibited a more diverse and modern lifestyle compared to non-user women. Furthermore, a relationship was identified between engagement in virtual space and lifestyle dimensions assessed in this study, including body image, leisure patterns, nutrition, social interactions, and physical activity. Conclusion: Differences and changes were observed in the lifestyles of the two groups, indicating that virtual space significantly influences the lifestyle of user women. This finding underscores the potential transformative effect of virtual engagement on women’s way of life.